Investigation of the frequency of molar incisor hypomineralisation in childhood celiac disease and evaluation with nutritional factors and calcium metabolism - Tok, Ayşegül; Altınsoy, Nilgün; Hoşnut, Ferda Özbay (Frontiers in Pediatrics, 2025)
BackgroundThe relationship between celiac disease and developmental enamel defects is complex and multifaceted. Although the presence of enamel changes in individuals with celiac disease is well documented, the exact etiology of these changes remains unclear. This study aims to investigate whether the enamel defects observed in children with celiac disease are due to malabsorption-related deficiencies or are a direct consequence of the autoimmune nature of celiac disease, thus informing the development of effective preventive strategies.Materials and methodsThis case-control clinical study included 150 children aged 3–18 years who were followed with a diagnosis of celiac disease, and 151 healthy controls with negative celiac serology, all evaluated at the Pediatric Gastroenterology Clinic between September 2023 and January 2025. The diagnosis of molar-incisor hypomineralization (MIH) was made based on the clinical criteria established by the European Academy of Paediatric Dentistry.ResultsCeliac disease diagnosis was confirmed through positive tissue transglutaminase IgA and anti-endomysial IgA antibodies, along with histopathological findings from upper gastrointestinal endoscopy. Among the celiac patients, 36.6% were newly diagnosed, 37.3% were compliant with a gluten-free diet, and 27% were non-compliant. Molar-incisor hypomineralization (MIH) was observed in 20.7% of the children with celiac disease, compared to 6% in the healthy control group. The likelihood of MIH occurrence in children with celiac disease was found to be 8.97 times greater than in healthy controls. MIH was most prevalent among newly diagnosed and non-compliant children with celiac disease, who also exhibited significantly lower vitamin D levels and elevated tissue transglutaminase values. However, there was no significant correlation between MIH prevalence and Marsh classification of intestinal damage.ConclusionMIH serves as a critical indicator of celiac disease, emphasizing the need for vigilant monitoring of vitamin D levels and dietary adherence to mitigate the development of MIH in affected individuals.